Cyto-palynological Studies in Taro (Colocasia esculenta (L.) Schott.)-An Overview - Beevi, P Nuzaifa (JOURNAL OF ROOT CROPS, 2014)
Taro (Colocasia esculenta (L.) Schott.) is an important tuber crop that can adapt well to different agroclimatic conditions. It is a vegetatively propagated crop with many morphotypes. The interrelationships between cytological and palynological features of individual plants have been used in solving several taxonomic problems. While number, size and morphology are the main chromosomal features of Karyomorphology, the shape and symmetry of pollen grains, the architecture of its wall, exine stratification, exine sculpture and structure, number, position and size and shape of aperture are some of the palynological features of taxonomic importance. Even though there were attempts in the cytological studies of taro, information available on the pollen morphology of taro is meagre and fragmentary. At the same time, there is considerable paucity of detailed cytotaxonomic work based on karyotype analysis at the sub specific level in taro. Sixty accessions of taro procured from three South Indian states and an exhaustive collection of a large number of accessions from all over India studied at the Central Tuber Crop Research Institute, Kerala, India, forms the basis of the present review. An attempt has been made in this review to document the major cytopalynological studies carried out so far in taro.